Co-infection of Atlantic salmon (Salmo salar) by Lepeophtheirus salmonis and Moritella viscosa - Hauge, Hege Sørvåg (The University of Bergen, 2019)
A co-infection is defined as an infection with two or more different pathogens, where the pathogens can either have a synergistic or antagonistic effect or alternatively not affect each other at all. Lepeophtheirus salmonis are the single largest problem found in salmonid farming today. It is a marine ectoparasitic copepod (Caligidae) occurring on both wild and farmed salmonids in cold temperate waters in the North Atlantic and North Pacific Ocean. They feed on mucus, skin and blood of their host leading to mild skin lesions that can disturb the osmotic balance. Moritella viscosa is a gram-negative bacterium thought to be the main agent causing winter ulcer disease in salmonids and occurs when water temperature is under 10 ºC. Clinical signs are necrosis of the skin, which advance to skin lesions on the flank, ranging from raised scales to larger lesions with exposed muscle tissue. This study looks at the co-infection of L. salmonis and M. viscosa and how these two pathogens affect growth, disease development (lice and ulcer number, size and severity) and transcription of immune genes. Study fish were sampled at four time points: (A) 5 days prior to infection, (B) 6 days post infection (dpi) L. salmonis; 7 dpi L. salmonis and 2 dpi M. viscosa [co-infection] dpi. (C) 26 dpi L. salmonis, 23 dpi M. viscosa [co-infection]. (D) 40 dpi L. salmonis, 37pi M. viscosa [co-infection]. During sampling, weight, length, condition factor (K-factor) was measured; lesions were counted, sized and graded; Lice were counted and staged. Transcription of immune genes Interleukin 1b (IL-1b), Interleukin 4 (IL-4), Interleukin 8 (IL-8), Interleukin 10 (IL-10), complement protein 3 (C3) and Immunoglobulin M (IgM). 2-ΔΔCt were analyzed from sampling B and C in skin and head kidney with Elongation factor α (EFα) as a reference gene. Results showed that a M. viscosa infection (both single and co-infected) did affect weight and k-factor compared to control and L. salmonis., but no differences between a M. viscosa single and co-infection. M. ...